Menilik lafal Sumpah Apoteker dan mentalitas calon apoteker - Najwa, Natasya Azizah (Maliki Interdisciplinary Journal, 2025)
This paper discusses the meaning of the pharmacist’s oath and its role in shaping the mentality and professionalism of prospective pharmacists from international, national, and Islamic jurisprudence (fiqh) perspectives. The pharmacist’s oath functions not only as a moral pledge but also as a spiritual commitment that guides pharmacists to uphold responsibility in their professional practice. Globally, the professional oath emphasizes universal ethical values and social responsibility, while in Indonesia it carries a stronger religious dimension through the acknowledgment of God. The perspective of Islamic health jurisprudence enriches this understanding by viewing the oath as a moral contract between humans and Allah, requiring integrity, honesty, and trustworthiness in pharmaceutical practice. The integration of the pharmacist’s oath, professional ethics, and fiqh principles is expected to produce pharmacists who are knowledgeable, ethical, and faithful, enabling them to compete globally without losing their Islamic spiritual values.